Mending Fences in the GCC-Iran Relationship in the Wake of Israel-Gaza War - Nora Maher (Policy Perspectives)
In the backdrop of the ongoing war in Gaza, the Gulf Cooperation Council (GCC) apparently shares more foundational grounds with Iran than with Israel, prompting a comprehensive reassessment of the GCC relations with Tehran. Employing the prisoner’s dilemma framework, the paper explores how hardline Gulf states could shift from a punitive stance toward Iran to a collaborative approach, encouraging cooperation over confrontation. The war in Gaza presents an ongoing dilemma to the governing regimes in the GCC trying to uphold both their domestic political stability vis-a-vis regional solidarity toward Palestine, and their international alliances. Ultimately, the GCC is urged to adopt a more measured and pragmatic approach toward Iran, considering potential pathways for cooperation, while carefully reconsidering the implications of normalization with Israel on broader Arab security concerns. The paper explores the prisoner’s dilemma as the theoretical basis for the cooperative paradigm and then investigates GCC and Iran dynamics in the wake of the Gaza War, highlighting the proximities between both sides, on which the GCC can capitalize. The paper, then, examines the GCC relations with Israel amid the ongoing war in Gaza, underscoring the threats that the GCC needs to recognize.